2016
DOI: 10.1902/jop.2015.150474
|View full text |Cite
|
Sign up to set email alerts
|

High Glucose Concentrations Suppress the Proliferation of Human Periodontal Ligament Stem Cells and Their Differentiation Into Osteoblasts

Abstract: The results of this study demonstrate that hyperglycemia inhibits human PDLSC proliferation and osteoblastic differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
49
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 41 publications
(80 reference statements)
5
49
0
1
Order By: Relevance
“…Our results together with previous findings 29,[40][41][42] postulate that impaired proliferation and osteoblast differentiation of cells present in the periodontium contributes to diabetes-associated spontaneous destruction of alveolar bone, whereas this impairment is improved by p-CA.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Our results together with previous findings 29,[40][41][42] postulate that impaired proliferation and osteoblast differentiation of cells present in the periodontium contributes to diabetes-associated spontaneous destruction of alveolar bone, whereas this impairment is improved by p-CA.…”
Section: Discussionsupporting
confidence: 85%
“…Incubating hPLFs at high glucose concentration also suppressed their proliferation and osteoblastic differentiation . Our results together with previous findings postulate that impaired proliferation and osteoblast differentiation of cells present in the periodontium contributes to diabetes‐associated spontaneous destruction of alveolar bone, whereas this impairment is improved by p ‐CA.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…While ligamental fibroblasts have been shown to exhibit a lowered proliferation rate when cultured for one week in a high glucose condition25, studies concerning short-term tenocyte culture within a day suggested no change in both proliferation and apoptosis1826. Our results demonstrated that tenocytes maintained similar growth rates between groups up to 14 days.…”
Section: Discussionmentioning
confidence: 45%
“…The small size of nodules and perturbation of calcium deposition imply that the high glucose concentrations alter osteoblastic bone formation, which increase the volume of immature mineralization similar to that of calcium deposition evoked by the presence of LPS [29][30][31][32] . Therefore, the only condition of high glucose concentration or stimulation by the P. gingivalis LPS is increased mineralization, but in both conditions, the mineralization had decreased.…”
Section: Discussionmentioning
confidence: 99%